The Effect of the Return of Serve on the Server Pair’s Movement Parameters and Rally Outcome in Padel Using Cluster Analysis - Ramón-Llin, Jesus; Guzmán, Jose Francisco; Llana, Salvador; Martínez-Gallego, Rafa; James, Nic; Vučković, Goran (Frontiers in Psychology, 2019)
Purpose: The pressure exerted on racket sports players by the service has been well documented. Whilst the return of serve has been suggested through qualitative interviews as being of similar importance (Vernon, Farrow & Reid, 2018) there is a dearth of quantitative data to support this contention. This study analysed time, speed and distance parameters related to the outcome of the return of serve (ROS) in Padel, a sport similar to tennis but played on a court bounded by walls and played in doubles format only. Methods: Matches (n=18) at two tournaments, sanctioned by the Valencian Federation, in 2012 were recorded and processed using Tracker software. ROS shot type (flat or lob), ball location, players’ positions on court and movement parameters between the ROS and the third shot of the server were captured 25 times per second. Results: Both lob and flat ROS produced six main clusters, as well as a small proportion of shots deemed outliers. The clusters differentiated shots played by two different level players (National and Regional), whether the ROS was played following a first or second serve, whether the serving pair adopted a conventional or Australian formation and whether the rally ended in a short number of shots (7 or less) or not. Conclusion: It was suggested that the aim of the ROS in Padel was to prevent the serving pair winning the rally quickly, since the advantage of the serve diminished after around 6 to 8 shots. This was best achieved by good depth on lobs, regardless of the direction, and pace on low shots, predominately aimed towards the server. This approach should be further modified to include the time between serve and ROS and consideration could be given to classifying attacking and defending positions.